2011
DOI: 10.1002/jhm.973
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with hospital care provided by hospitalists and primary care physicians

Abstract: BACKGROUND: Compared to hospital care provided by primary care physicians (PCPs), the hospitalist model provides equal-to-superior efficiency and outcomes; however, little is known about how the model affects patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Kindness of health care professionals and communication between patient and attending physician were mentioned in several studies as important factors for satisfied patients [66][67][68][69]. Unfortunately, as shown in our previously performed time and motion studies, little time has been used for doctor-patient interaction [28,29,[31][32][33][34].…”
Section: Patient Satisfactionmentioning
confidence: 94%
“…Kindness of health care professionals and communication between patient and attending physician were mentioned in several studies as important factors for satisfied patients [66][67][68][69]. Unfortunately, as shown in our previously performed time and motion studies, little time has been used for doctor-patient interaction [28,29,[31][32][33][34].…”
Section: Patient Satisfactionmentioning
confidence: 94%
“…In hospitals with no DGIM, similar to Fukuchiyama City Hospital prior to the establish-ment of the DGIM, there is no choice but to have such patients treated by full-time specialists whose specialty typically lies outside of the target disease. From the perspective of patient satisfaction, no differences are observed between treatment by a hospitalist or primary care physician (15). Considering the possibility that the presence of a DGIM at a central hospital may make it easier for organ specialists to administer their care (16), particularly against the backdrop of the physician shortage, promoting the establishment of DGIMs may be a solution for improving the quality of regional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…3 6 Many studies have found that hospitalists significantly decrease lengths of stay and costs without harming quality and patient satisfaction. [6][7][8][9] In addition to the generally favourable outcome data, several other developments in the US promoted hospitalist growth. When hospitals came under pressure to improve their quality and safety, hospitalists embraced these tasks and became recognised leaders in them.…”
Section: Factors Driving the Growth Of The Hospitalist And Acute Medimentioning
confidence: 99%
“…6-8 20 Other evidence shows that medical education improves, patient satisfaction is neutral, and the effects on quality are mixed. [6][7][8][9] Acute medical units in the UK have been associated with lower inpatient mortality, improved patient and staff satisfaction, reduced hospital stays, and increased throughput. 14 15 21 Although there are no controlled studies comparing generalist care with subspecialty care, there is good evidence that generalist care is less expensive.…”
Section: Theoretical and Empirical Rationalementioning
confidence: 99%